A GRAPHOLOGICAL DEVIATION OF ANDRE RADITYA’S LIFE SIGNS (A STYLISTIC APPROACH) - ANANTHA, ALDINO DENNY (LANTERN (Journal on English Language, Culture and Literature), 2014)
The writer interested on examines Andre Raditya’s motivational book due to its language exclusivity in presenting the materials. Usually, most of the motivational book writers are focusing on the book’s contents rather than the use of language. In this book, the author attracts his readers by using different style of language than the motivational book writers in general. The different style of writing is clearly seen on the graphological point of view by adding some effects, such as deliberate misspelling to present some specific meaning.